In vitro propagation of Codonopsis pilosula (Franch.) Nannf. using apical shoot segments and phytochemical assessments of the maternal and regenerated plants - Roggers, Gang; Richard, Komakech; Yuseong, Chung; Denis, Okello; Wook, Jin Kim; Byeong, Cheol Moon; Nam, Hui Yim; Youngmin, Kang (BMC Plant Biology, 2023)
Background Codonopsis pilosula (Franch.) Nannf. is a medicinal plant traditionally used in China, Korea, and Japan to treat many diseases including poor gastrointestinal function, low immunity, gastric ulcers, and chronic gastritis. The increasing therapeutic and preventive use of C. pilosula has subsequently led to depletion of the natural populations of this species thus necessitating propagation of this important medicinal plant. Here, we developed an efficient and effective in vitro propagation protocol for C. pilosula using apical shoot segments. We tested various plant tissue culture media for the growth of C. pilosula and evaluated the effects of plant growth regulators on the shoot pro‑ liferation and rooting of regenerated C. pilosula plants. Furthermore, the tissues (roots and shoots) of maternal and in vitro‑regenerated C. pilosula plants were subjected to Fourier‑transform near‑infrared (FT‑NIR) spectrometry, Gas chromatography‑mass spectrometry (GC–MS), and their total flavonoids, phenolics, and antioxidant capacity were determined and compared. Results Full‑strength Murashige and Skoog (MS) medium augmented with vitamins and benzylaminopurine (1.5 mg·L−1 ) regenerated the highest shoot number (12 ± 0.46) per explant. MS medium augmented with indole‑ 3‑acetic acid (1.0 mg·L−1 ) produced the highest root number (9 ± 0.89) and maximum root length (20.88 ± 1.48 mm) from regenerated C. pilosula shoots. The survival rate of in vitro-regenerated C. pilosula plants was 94.00% after acclimatization. The maternal and in vitro‑regenerated C. pilosula plant tissues showed similar FT‑NIR spectra, total phenolics, total flavonoids, phytochemical composition, and antioxidant activity. Randomly amplified polymorphic DNA (RAPD) test confirmed the genetic fidelity of regenerated C. pilosula plants. Conclusions The proposed in vitro propagation protocol may be useful for the rapid mass multiplication and production of high quality C. pilosula as well as for germplasm preservation to ensure sustainable supply amidst the ever‑increasing demand